The Peripheral NK Cell Repertoire after Kidney Transplantation is Modulated by Different Immunosuppressive Drugs - Neudoerfl, Christine; Mueller, Bernadett J.; Blume, Cornelia; Daemen, Kerstin; Stevanovic-Meyer, Maja; Keil, Jana; Lehner, Frank; Haller, Hermann; Falk, Christine S. (Frontiers in Immunology, 2013)
In the context of kidney transplantation, little is known about the involvement of natural killer (NK) cells in the immune reaction leading to either rejection or immunological tolerance under immunosuppression. Therefore, the peripheral NK cell repertoire of patients after kidney transplantation was investigated in order to identify NK cell subsets that may be associated with the individual immune status at the time of their protocol biopsies for histopathological evaluation of the graft. Alterations in the peripheral NK cell repertoire could be correlated to the type of immunosuppression, i.e., calcineurin-inhibitors like Cyclosporin A vs. Tacrolimus with or without addition of mTOR inhibitors. Here, we could demonstrate that the NK cell repertoire in peripheral blood of kidney transplant patients differs significantly from healthy individuals. The presence of donor-specific antibodies was associated with reduced numbers of CD56dim NK cells. Moreover, in patients, down-modulation of CD16 and CD6 on CD56dim NK cells was observed with significant differences between Cyclosporin A- and Tac-treated patients. Tac-treatment was associated with decreased CD69, HLA-DR, and increased CD94/NKG2A expression in CD56dim NK cells indicating that the quality of the immunosuppressive treatment impinges on the peripheral NK cell repertoire. In vitro studies with peripheral blood mononuclear cells of healthy donors showed that this modulation of CD16, CD6, CD69, and HLA-DR could also be induced experimentally. The presence of calcineurin or mTOR inhibitors had also functional consequences regarding degranulation and interferon-γ-production against K562 target cells, respectively. In summary, we postulate that the NK cell composition in peripheral blood of kidney transplanted patients represents an important hallmark of the efficacy of immunosuppression and may be even informative for the immune status after transplantation in terms of rejection vs. drug-induced allograft tolerance. Thus, NK cells can serve as sensors for immunosuppression and may be utilized for future strategies of an individualized adjustment of immunosuppression.